Environmental effects on mechanical, thermophysical and electrical properties of epoxy resin filled with carbon nanofillers - Glaskova-Kuzmina, Tatjana; Aniskevich, Andrey; Sevcenko, Jevgenijs; Zotti, Aldobenedetto; Borriello, Anna; Zarrelli, Mauro (AIP Publishing, 2019)
The aim of this work was to establish the effect of environmental factors (moisture and temperature) on some mechanical, electrical and thermal properties of epoxy-based composites filled with carbon nanofillers: nanotubes (CNT), nanofibers (CNF) and hybrid nanofiller (nanotubes/nanofibers in the ratio 1:1) and to reveal the most environmentally stable NC. First, the nanocomposites (NC) containing different nanofiller contents were prepared to evaluate electrical percolation threshold and to choose NC at certain electrical conductivity for further characterization of the physical properties in initial state and during/after environmental ageing. The environmental ageing consisted of water absorption at 70 °C until equilibrium moisture content reached all samples in 4 weeks and 2) heating at 70 °C for the same time, and 3) freezing at -20 °C for 8 weeks. Two concurrent factors, temperature and moisture, led to post-curing of all materials studied without significant plastization. Some positive nanofiller effects were found for sorption, mechanical and thermophysical characteristics of RTM6 epoxy resin. Based on experimental results, the most environmentally stable NC was epoxy filled with 0.1 wt. % of CNT/CNF hybrid, which had the lowest effect of temperature and moisture on thermal and electrical conductivities, along with the lowest equilibrium water content and diffusivity.
Keywords: environmental ageing; mechanical properties; electrical properties; thermophysical properties; carbon nanofillers; epoxy